Effect of Dietary Magnesium on the Association Between Serum Uric Acid and Female Infertility - Xin X; Zhang Q; Xu J; Huang J (International Journal of Women's Health)
Xiaoqin Xin,1 Qi Zhang,2 Jing Xu,1 Jungao Huang3 1Department of Clinical Laboratory, Ganzhou People’s Hospital, Ganzhou, Jiangxi, People’s Republic of China; 2Department of Obstetrics and Gynecology, Ganzhou Maternal and Child Health Hospital, Ganzhou, Jiangxi, People’s Republic of China; 3Department of Medical Genetic, Ganzhou Maternal and Child Health Hospital, Ganzhou, Jiangxi, 341000, People’s Republic of ChinaCorrespondence: Jungao Huang, Email jungaohuang@sina.comBackground: Few studies have evaluated the correlation between serum uric acid (SUA) levels and the prevalence of female infertility in the general population, and the effect of magnesium intake on this correlation has not been investigated.Methods: All participants aged 18– 45 years at baseline were enrolled from the National Health and Nutritional Examination Surveys (NHANES) 2013– 2018. The continuous variable of SUA was divided into quartile (Q1: ≤ 3.7 mg/dL, Q2: 3.7– 4.4 mg/dL, Q3: 4.4– 5.1 mg/dL, Q4: ≥ 5.1 mg/dL). Multivariable logistic regression was used to estimate odds ratios (OR) and 95% confidence intervals (CI). Dietary magnesium was divided into two groups based on the median number of participants (low magnesium intake, < 243 mg/day; high magnesium intake, ≥ 243 mg/day).Results: A total of 3185 female participants were included in the final analysis, 10.58% of whom were infertile. In the full adjustment model, SUA was positively associated with female infertility (OR=1.13, 95% CI: 1.01– 1.27). Compared to the lowest quartile (Q1), female participants with the highest SUA levels (Q4) had an increased risk of infertility by 62% (OR=1.62, 95% CI: 1.1– 2.4). Moreover, we found an interactive effect of magnesium intake on the association between SUA and infertility in adjusted models (interaction likelihood ratio test: P=0.029), implying that high magnesium intake may ameliorate the association between SUA and female infertility.Conclusion: This study is the first to report an interactive effect of dietary magnesium intake on the relationship between SUA and female infertility.Plain Language Summary: Infertility affects approximately 15% of reproductive-aged couples worldwide. Few studies have evaluated the correlation between serum uric acid (SUA) levels and the prevalence of female infertility in the general population. The role of magnesium on infertility through its effects on uric acid has not been investigated. We found SUA was positively associated with female infertility in the present study and an interactive effect of magnesium intake on the association between SUA and infertility existed, which implied that high magnesium intake may ameliorate the association between SUA and female infertility. The study casts a light on how magnesium affects infertility, hinting at the importance of supplementing with magnesium in various ways.Keywords: serum uric acid, infertility, dietary, magnesium